[PP.36.21]: ATRIAL FIBRILLATION OUTPATIENT CLINIC FOR HYPERTENSIVE PATIENTS SUBMITTED TO ORAL ANTICOAGULATION. ONE YEAR EXPERIENCE IN TUSCAN AREA. (June 2015) - Conti>, A.>; Bianchi, S.; Grifoni, C.; Trausi, F.; Angeli, E.; Paolini, D.; Catarzi, S.; Perrotta, M.E.; Covelli, A.; Renzi, N.; Bertolini, P.; Mazzucchelli, M.
Abstract : Objective: Atrial Fibrillation (AFib), older-age, and hypertension frequently coexist. Due to the CHADSDVASc-score and high-risk of ischaemic-stroke, prevention of systemic-embolism is mandatory just at the time of the first presentation to the Emergency Department(ED). Warfarin(W) need close activity-monitoring and showed substantial risk-of-bleeding; thus W is prescribed only to half-of-patients who need it and another half drop out of the treatment during the firsts months or show poor INR-control. The New-Oral-Anti-Coagulants(NOACs) showed non-inferiority to W in ischaemic-stroke prevention and smaller bleeding risk. Aim of the present study was to analyze the efficacy and safety of the two treatments in patients managed with a ED Afib-Outpatient-Clinic. Design and method: Non-randomized AFib patients were managed according to International-Guidelines, CHADSDVASc-score and the physician on duty. They were followed-up to short- and long-term. Patients with moderate-to-severe valvulopathy were excluded. The primary end-point was cardio-embolic event at the follow-up; secondary endpoints were mayor-bleeding, non haemorragic side-effects and patient's satisfaction for the treatment. Results: Between July-2013-and-July-2014, 435 patients were enrolled; 384(88%) received anticoagulation (157 with NOACs, group-A and 227 with W, group-B); the remaining 51(12%) were not submitted to anticoagulation. Patients of group-A compared with group-B were older (77 ± 8 y vs 74 ± 11 y, p = 0.001, respectively) and showed higher prevalence of hypertension (88% vs 76%, p = 0.005, respectively). Group-A versus group-B showed higher CHADSDVASc-score (4.0 ± 1.4 vs 3.1 ± 1.5, p < 0.001, respectively) and higher HASBLED-score (3.3 ± 1.1 vs 1.8 ± 1.0, p < 0.001, respectively). At the long-term, 8 events occurred as follows: 6 (1%) mayor-bleeding (1 in group-A and 5 in group-B, p = NS), 2 ischaemic-stroke (1 in both groups). Interestingly, in the group-A, only 2 (1%) patients never started the treatment and 20 (13%) drop-out of the recommended treatment. When compared to the group-B, 47 (22%) patients never started the treatment, 25 (12%) drop-out of the recommended treatment, and 13 (6%) showed poor INR control (overall, 22 vs 75 patients, p = 0.001). Also satisfaction for the treatment was significantly higher in the group-A than in the group-B. Conclusions: Patients receiving NOACs and Afib-Outpatient-Clinic management showed higher satisfaction for the recommended treatment, non-inferior efficacy and safety when compared to W.